Mobility and Walkability: An Analysis OF Urban Design Elements around Divisoria, Cagayan de Oro - Eltanal, Ar. Romel (JPAIR Multidisciplinary Research, 2019)
Mobility and Walkability is an important concept in urban planning. The term is built around the concept of providing healthy communities, reducing dependency on automobiles and improving health consciousness to people. Based on factors including connectivity, densities, amenities, and socio-economics, this research focused on the analysis of urban design elements in relation to mobility and walkability of pedestrians around Divisoria District, Cagayan de Oro City through the influence of street networks around the area. Using data and actual survey helped locate high rates for walkability within the district. Additional qualities such as distance, safety, socio-economic and public spaces also play a role in the rates of mobility and walkability around the district. The urban design elements as facilitators take place within all types of developments around the area, but the number of barriers hinders mobility and walkability. Analysis of barriers and facilitators produced design guidelines that will promote mobility and walkability for new districts and urban development in the future. The findings suggested that urban design elements are important in achieving mobility and walkability.